IDENTITY CRISIS IN LAUREN MYRACLE'S UNDER THE MOON: A CATWOMAN TALE - Mauludi, Anugrah Bulan; Pandin, Moses Glorino Rumambo; Wulan, Nur; Christinawati, Christinawati (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2024)
This article was conducted to study about the phenomenon of identity crisis through the portrayal of a literary work’s main character in Lauren Myracle’s Under the Moon: A Catwoman Tale. The trauma of the main character affected her behaviour to be maladaptive. It also affected the main character’s identity crisis in her dream and fantasy. Furthermore, her identity crisis is fixated by the initiative versus guilt and the industry versus inferiority stages of development.